Efektivitas Penggunaan Media Pembelajaran Wordwall Untuk Meningkatkan Motivasi Belajar IPAS - Taryzca Putri Laela Ramadhani; Angel Maria VK; Cantika Dinova Ramadila; Desi Eka Pratiwi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine how effective the interactive learning media Wordwall is in increasing students' learning motivation in the subject of Natural and Social Sciences (IPAS) in elementary schools. Wordwall provides interesting educational game features, so it is expected to arouse students' interest and enthusiasm in learning IPAS. This study uses an experimental method with a pre-test and post-test design in the control and experimental groups. Participants in this study were fourth grade students in an elementary school. Data on students' learning motivation were collected through questionnaires and analyzed using statistical tests to see the difference in increased motivation between the group using Wordwall and the group using conventional methods. The results showed that the use of Wordwall significantly increased students' learning motivation compared to conventional learning methods. Therefore, Wordwall can be an effective alternative learning media to support students' learning motivation in the subject of IPAS in elementary schools.